Affective disorder: The politics of unprincipled emotion in Glauber Rocha's Terra em transe. Issue 1 (March 2020) - Posso, Karl
Abstract : Caetano Veloso claims that the outrage or 'trauma' Glauber Rocha's film Terra em transe ['Entranced Earth'] (1967) provoked, particularly amongst Brazil's left-wing intelligentsia, precipitated the varied forms of countercultural production known as Tropicália. This article examines how the film articulates its 'traumatic' political and ethical agenda through the manipulation of sensation and emotion, especially through its unlikely insistence on love in the midst of political turmoil. The article maintains that by espousing what might be termed an affective art of relationality, Rocha appears less concerned with representing transcendent ideals and more with generating affects, qualities of feeling or sensations, which resist categorical interpretation. This resistance to, or disruption of, representation and epistemological conventions through affect in Terra em transe constitutes an attempt to intervene ethically and politically in the world in a non-partisan fashion. This article redresses gaps in widely accepted readings of one of the most important films in the history of Brazilian cinema and seeks to expand the discussion of affect theory in the context of cinema.